Microscopic and neuroendoscopic treatment of a large ruptured supratentorial dermoid cyst with extensive dissemination: a case report and literature review - Zhang, Yuhang; Deng, Tingzhen; Wu, Zhi; Yang, Haijun; Ma, Xingyuan; Wang, Yatao; Ding, Ruiwen; Li, Haotian; Wang, Dawen (Frontiers in Oncology, 2024)
Introduction and importanceIntracranial dermoid cysts are rare, constituting 0.04% to 0.6% of all intracranial tumors. They often arise from ectodermal cells trapped during neural tube formation. We report a case of spontaneous rupture of a large tentorial epithelioid cyst, which caused massive dissemination of liquid cholesterol into the subarachnoid cisterns and ventricles.Presentation of caseA 28-year-old male presented with a two-week history of headache and memory decline. CT and MRI revealed a 9x6 cm lesion in the left frontotemporal region with widespread dissemination of lipid droplets. Surgical resection was performed using a microscope combined with a neuroendoscope. Pathology confirmed a dermoid cyst.Clinical discussionRuptured dermoid cysts can cause significant symptoms due to the dissemination of cyst contents. Imaging is crucial for diagnosis and surgical planning. The combined microscopic and neuroendoscopic approach minimized blind spots and allowed thorough tumor exposure, facilitating complete resection with minimal residual complications. Postoperative outcomes were favorable, with imaging confirming substantial tumor removal and restored cerebrospinal fluid circulation.ConclusionPrompt diagnosis and comprehensive surgical intervention are essential for managing ruptured intracranial dermoid cysts. Combined microscopic and neuroendoscopic techniques are effective in achieving extensive resection and reducing complications.